Behavioral strategy - Powell, Thomas C.; Lovallo, Dan; Fox, Craig R. (Strategic Management Journal, 2011)
Abstract Behavioral strategy merges cognitive and social psychology with strategic management theory and practice. Despite much progress, the aims and boundaries of behavioral strategy remain unclear. In this paper we define behavioral strategy and identify the main unsolved problems. We propose a unifying conceptual framework for behavioral strategy and conclude by introducing the papers of the Special Issue on the Psychological Foundations of Strategic Management. Copyright © 2011 John Wiley & Sons, Ltd.